Coextensividade: sobre as noções de tempo na educação - Neuscharank, Angelica (2019)
This research proposed to work with the notion of co-extensivity in order to problematize the ideas of time in education, thinking of it through an anionic time, with the concepts of duration, coexistence, and the eternal return. The conceptual twists developed are related to the movement of looking to education along with the reasoning of the philosophies of difference by authors such as Gilles Deleuze, Félix Guattari, Henri Bergson, and Friedrich Nietzsche. As research problem, the following question has been established: what can co-extensivity produce as effect with the notions of time in a research in Education? Thus, the process of mining has been used as a methodological possibility, a creative selection movement towards the modes of existence of a researcher-teacher in provisional space-time, telling about her affective collection of readings, images, objects, speeches, and other heterogeneity that would capture her to compose a writing with them. This is a method that problematizes the ways we naturalize the thought that judges, analyzes, systematizes, and ignores the shapeless, unpredictable, uncertain, unstable, and incalculable in life. The thesis in this dissertation, therefore, by articulating mined heterogeneous in the research as a thought that surrounds the time being, taking it as living, unfinished organism, becomings of living entities (organic or not) produced by creative involution, thinks an education in which different relations with time are sheltered, an education that is captured by chronology but also extrapolating it, inventing intervals within pontualities and specific hours to try out 'creative time losses'. Time is detached from a straight, evolutive, and progressist line that will not lead to a sad return of a past and the apology to a future, so that these segments are broken to think only on durations. This is time attached to life, imperceptible by the eye just like breathing, but axial to existence.